Effect of Some Synthesized Pyrrolidines in Growth of L. infantum Promastigotes - Haitham L. Al-Hayali; Abdulwahhab J. Al-Hamadany; Muntaha M. Al-Kattan (Tikrit Journal of Pure Science, 2023)
In this research, three pyrrolidine compounds (P1-P3) were synthesized and then tested for efficacy against L. infantum promastigotes in vitro.